Penggunaan Kortikosteroid pada Pasien Anak dengan Perikarditis Tuberkulosis. - Novi Violona Edwar; Abi Andayu; Finny Fitry Yani (Jurnal Ilmu Kesehatan Indonesia, 2021)
Tuberculous pericarditis (TB pericarditis) is a disease that still frequently occurs in developing countries. The mortality rate due to TB pericarditis is still quite high, reaching 17-40%. Death due to tuberculous pericarditis is influenced by adequate or not treatment. The use of additional corticosteroid therapy is still a matter of debate in the treatment of tuberculous pericarditis. Writing this case aims to see the outcome of the use of corticosteroids in patients with tuberculous pericarditis. Literature searches were carried out through Pubmed and Google Scholar. From the results of literature search, two meta-analyzes were obtained that discussed the use of corticosteroids in tuberculous pericarditis. In children with tuberculous pericarditis, the use of corticosteroids does not reduce mortality, but can reduce complications due to tuberculous pericarditis. Keywords: corticosteroids, tuberculous pericarditis, outcome.